Novel de novo heterozygous FGFR1 mutation in two siblings with Hartsfield syndrome: A case of gonadal mosaicism. Issue 9 (28th May 2014) - Dhamija, Radhika; Kirmani, Salman; Wang, Xiangling; Ferber, Matthew J.; Wieben, Eric D.; Lazaridis, Konstantinos N.; Babovic‐Vuksanovic, Dusica
<x xml:space="preserve">Abstract</x> Hartsfield syndrome has been recently reported to be associated with mutations in FGFR1 however, to this date; no familial cases have been reported. In this report, we describe two siblings with Hartsfield syndrome and a novel de novo FGFR1 mutation suggesting gonadal mosaicism. The proband presented at our institution at age 6 years with a clinical diagnosis of Hartsfield syndrome and requesting further genetic evaluation. Previous studies included a normal karyotype, oligonucleotide array, and single gene testing for nonsyndromic holoprosencephaly (SHH, SIX3, ZIC2, TGIF). At the age of 6 years, exome sequencing was performed and a de novo novel missense variant was identified in FGFR1 (coding for fibroblast growth factor‐1) on chromosome 8p12: c.1880G>C (p.R627T). Subsequently, a younger sibling was born with the same phenotype (holoprosencephaly, ectrodactyly of bilateral hands and feet and bilateral cleft lip and palate). Targeted sequencing of FGFR1 revealed the identical variant that was previously identified in the proband. To our knowledge this observation is the first documentation of familial recurrence of Hartsfield syndrome. As both parents were negative for the sequence variant in FGFR1 gene by testing peripheral blood samples, this suggests gonadal mosaicism. The frequency of gonadal mosaicism in Hartsfield syndrome is not known however given our case, this possibility should be taken in to consideration for recurrence risk estimation in children of clinically unaffected parents. © 2014 Wiley Periodicals, Inc.